On Annihilator-Extending Modules - Qasim, Yousef A.; Yaseen, Sahira M. (Iraqi Journal of Science, 2022)
Throughout this work we introduce the notion of Annihilator-closed submodules, and we give some basic properties of this concept. We also introduce a generalization for the Extending modules, namely Annihilator-extending modules. Some fundamental properties are presented as well as  we discuss the relation between this concept and some other related concepts.